Enhancement of thermal spin transfer torque by double-barrier magnetic tunnel junctions with a nonmagnetic metal spacer. (14th November 2016) - Chen, C H; Tseng, P; Yang, Y Y; Hsueh, W J
Abstract: Enhancement of thermal spin transfer torque in a double-barrier magnetic tunnel junction with a nonmagnetic-metal spacer is proposed in this study. The results indicate that, given the same temperature difference, thermal spin transfer torque and charge current density for the proposed double barrier magnetic tunnel junction configuration can be approximately twice as much as that of the traditional single-barrier magnetic tunnel junctions. This enhancement can be attributed to the resonant tunneling mechanism in the double-barrier structure.